Implementasi Strategi Kasus Digital Dalam Mengembangkan Literasi Kewarganegaraan Mahasiswa - Kemil Masi, Thomas; Badhe, Maria Frida; Putri Benu, Rosita; Yuce Sawak, Yanuaria (Universitas Muhammadiyah Ponorogo, 2026)
This study aims abstract to examine the effect of implementing digital case study strategies on developing civic literacy among students of the Civic Education Study Program, Faculty of Teacher Training and Education, Nusa Cendana University. This research employed a quantitative approach with a quasi-experimental design. A questionnaire was used as the instrument to measure students’ civic literacy levels. The validity test showed a significance value of 0.836 (>0.05), indicating that the instrument was valid. The reliability test obtained a Cronbach’s Alpha value of 0.947 (>0.60), showing the instrument’s kreliability. ANOVA results indicated a significance value of <0.01, revealing significant mean differences between variables. The simple linear regression test produced a significance value of 0.001 (<0.05), demonstrating a significant effect of digital case study strategy implementation on civic literacy. Therefore, the digital case study strategy effectively enhances students’ civic literacy.